Comparison of gelatinization method, starch concentration, and plasticizer on physical properties of high‐amylose starch films. (15th November 2017) - Zhong, Yuyue; Li, Yibo; Liang, Wenxin; Liu, Linsan; Li, Silu; Xue, Jiquan; Guo, Dongwei
Abstract: High amylose starch is a potential material to produce biodegradable films with the better physical properties than normal starch. In this research, Taguchi's design and analysis of variance were used to compare the effects of gelatinization methods, starch concentrations, and plasticizers on physical properties of high amylose starch films. The results showed that the gelatinization method was the most significant factor for transparency, and the highest transparency was obtained through high temperature‐high pressure treatment. The starch concentration impacted farthest on thickness, tensile strength, elongation at break, and solubility in oil. The highest thickness and tensile strength were obtained from 10% starch concentration, the highest elongation at break were created by 5% concentration, and the lowest solubility in oil was produced by 2% concentration. Solubility in water was affected by plasticizers most, especially in xylitol. The information in this study is helpful to choose optimal parameters for preparing high amylose starch films with desired physical properties. Practical applications: Due to the biodegradable and environmentally‐friendly traits, high‐amylose starch film is a promising alternative to plastic film. Most studies were focused on the changing of one of the independent parameters at a time while maintaining the others at fixed levels. However, studying the interactive effects of these parameters is beneficial to the development of high‐amylose starch films at a whole insight. For this purpose, the effects of different preparation parameters under different levels on physical properties of high‐amylose starch film were studies under Taguchi design in this study. Results showed the different effects of gelatinization methods, starch concentrations, and plasticizers on different properties such as mechanical properties, solubility in water and oil, and transparency of high‐amylose starch films. The information provided by this study will play a guiding role for the production of high‐amylose starch films in different applications with optimal parameters.